Storage and Temperature Stability of Emulsified Biodiesel-Diesel Blends - Maji, Nitai C.; Rastogi, Preetika; Krishnasamy, Anand; Aidhen, Indrapal Singh; Kaisare, Niket S.; Basavaraj, Madivala G. (American Chemical Society, 2022)
The scarcity of fossil fuel has led to the recent worldwide commercialization of biodiesel-blended diesel. The benefits associated with emulsion fuels have encouraged researchers to study the blended emulsified fuels in diesel engines. Recent results show the effectiveness of blended emulsified fuels in terms of better fuel economy and less harmful emissions. Investigation on the stability of these blended emulsified fuels during storage in the fuel tank is equally crucial for commercialization and practical application. A systematic study on the storage stability of water in biodiesel/diesel blend nanoemulsions (nEs) is presented in this work. A mixture of two biodegradable surfactants, Span 80 and Tween 80, is used to stabilize the nEs. The nEs are formulated by subjecting a mixture of 5 vol % of each surfactant, 5 vol % of water, and 85 vol % of pure or blended diesel to high shear homogenization at 5000 rpm for 2 min. Storage stability of the emulsified fuels is studied for 65 days at 25 °C with the help of dynamic light scattering and viscosity measurements. The mean droplet size increases, and the stability decreases with an increase in the biodiesel concentration. The smallest mean droplet size is 32 nm for emulsified fuel using pure diesel, and these emulsions remain stable for 65 days. No macroscopic phase separation is observed for any sample aged for 24 days. A moderate increment in droplet sizes is observed during this period. The droplet size increases significantly when more than 15 vol % biodiesel is used in the fuel blend. Those samples show stratification after 65 storage days. An increment in the zero-shear viscosity of the samples over aging helps hinder the rapid coalescence of the droplets, thus preventing phase separation. Furthermore, the thermal stability of the samples is also investigated at elevated temperatures up to 50 °C. The nEs are found to be highly stable within this temperature range and showed a moderate change in mean droplets size, especially when the concentration of biodiesel in the emulsified fuel blend is less than 15 vol %.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Emulsified Biodiesel-Diesel; biodiesel-blended diesel; emulsion fuels; blended emulsified fuel; biodegradable surfactants